Profile of patients diagnosed as sepsis (ICD X: A41.9) in the Internal Medicine Ward Sardjito Hospital in 2002 - Yanri Wijayanti Subroto Yanri Wijayanti Subroto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Sardjito Hospital as the top referral hospital for the Yogyakarta Special Province and the southern part of Central Java has a mortality rate of 56.83% of patients diagnosed as sepsis (ICD X A41.9). The overall hospital sepsis case in the year 2002 was 275, with 50.54% (139) of which was treated in the Internal Medicine ward. Out of the 139 cases, 44.60% was man and 55.40% was woman. Method: This study was focused on the identification of demographic and clinical factors of patients diagnosed as sepsis (ICD X A41.9) in Internal. Medicine ward Sardjito Hospital in 2002. Demographic data include sex, age, system of hospital admission (referral or self admition. Clinical data include the concomitant disease(s), causes of death, and type of cultured microorganism(s). The identification of these factors may be beneficial for designing an early warning system for fatal cases of patients with sepsisResults: Only 120 (86.33%) out of 139 medical records were eligible for further analysis. Seventy-one (59.17%) patients died in the hospital, whereas 49 (40.83%) were discharged from the hospital, but mostly were forced leave (only 6 patients were discharged in a good condition). The median ± SD age was 53.5 ± 15.99 years old with the youngest age was 17 and the oldest was 98. More than 50% of patients were above 50 years old. As many as 72 (60%) patients were admitted to the hospital referred by other hospitals (a few numbers were referred by private physicians), and only 48 (40%) patients were self-admitted. The average length of hospitalization was 6.96 ± 5.43 days, with the range of 1-25 days. The cause of death of these patients were mostly septic shock (61.97%), followed by respiratory failure (19.72%), intracranial process (14%), cardiac arrest (2.8%) and MOFS (1.4%). The underlying/concomitant diseases are:. gastrohepatology (mostly hepatic cirrhosis and hepatocellular carcinoma); hematology (acute leukemia, multiple myeloma), pulmonology (TB, COPD, pneumonia), oncology (Ca mammae, Ca cervix); endocrinology (DM type 2 with ulcus diabeticum), nephrology (chronic renal failure), cardiology (congestive heart failure), obsgyn (septic puerpuralis) and trop-med (urinary tract infection, malaria), etc.Conclusion: We report here research on medical record of patients diagnosed as sepsis (ICD X: A41.9) in Internal Medicine ward Dr. Sardjito Hospital in 2002. There were 139 cases with only 120 were eligible for analysis. Mortality reached 59.17% of cases with median of age 53.5 years and average length of hospitalization of 6.96 days. The most common cause of death was septic shock and gastrohepatology as the most common comorbid disease.Key words: sepsis-demographic-clinical presentation-cause of death